Implementasi Algoritma Branch and Bound Pada Aplikasi Mobile Pemandu Wisata Untuk Pengembangan UMKM Jawa Barat - Sepriyadi, Adi; Sujjada, Alun; Somantri, Somantri (Building of Informatics, Technology and Science (BITS), 2024)
Tourism is a crucial economic sector in Indonesia, contributing significantly to economic growth and foreign exchange. In 2022, the number of domestic tourist visits reached 734.86 million, up 19.82% from the previous year. East Java recorded the most visits with 198.91 million trips, followed by West Java (128.66 million) and Central Java (103.99 million). However, tourist destinations in West Java are less well known due to a lack of information, hampering tourism potential and the development of local MSMEs. To overcome this problem, an Android-based guide application was developed that integrates information on tourist destinations and MSMEs in West Java. This application uses the Branch and Bound algorithm to facilitate the selection of the closest route from tourist sites to several MSMEs efficiently and accurately. This research identifies the lack of information as the main obstacle to tourism development in West Java. Application development and testing showed the effectiveness of the Branch and Bound algorithm in determining the closest route. The implementation of this application increases access to tourist information and MSMEs, as well as the income of local MSME players related to tourism. The application is expected to contribute positively to the development of tourism and MSMEs in West Java and become a model for the development of similar applications in other regions in Indonesia.